Neonatal idiopathic aneurysm of the common iliac artery - Krysiak, Remigiusz (J Vasc Surg Cases Innov Tech, 2019)
Arterial aneurysms are very rare in children, with iliac aneurysms being even more uncommon. We report the case of a 61-day-old girl with a right common iliac artery aneurysm that was an incidental finding on the third day of life. The aneurysm was treated by direct aneurysm puncture and endovascular coil embolization. The patient was discharged with no complications, and complete exclusion of the aneurysm was confirmed on the 3-month follow-up examination.